Victorian Social Life as Reflected in George Elliot’s Adam Bede and Silar Marner - Endang Suciati (Unipdu Jombang, 2025)
This article examines the representations of Victorian social life in George Eliot’s Adam Bede and Silas Marner particularly on social class, gender relation, religious life, rural community, as well as the role of setting and language in constructing Victorian social reality. Using narratological framework, this article analyzes the interwind between fabula, actors, and setting to reveal how Victorian values are articulated through the narrative structure. The result shows that both novels present the interaction among upper, middle, and lower-class characters, and also highlight women’s position in Victorian society, especially in terms of marriage, economic security, and moral expectations. Rural community is portrayed as a space of shared values, like sympathy and respect. Religion, especially Methodism, becomes significant moral force that influences the individual behavior and communal norms. The setting and the language also reflect the social life of Victorian era. This article argues that the narrative structure in those novels not only reveal the social values but also presents the problems occurred within early to middle Victorian society